Training and Planning for Successful Breastfeeding among Pregnant Women - Maryam Saberi; Fatemeh Vizeshfar; Zahra Keshtkaran (Journal of Health Sciences and Surveillance System, 2022)
Background: Breastfeeding training among mothers is necessary to ensure the continuation of this behavior. Given the great benefits of breastfeeding for children and mothers and the effective role of training in this process, studies have emphasized the importance of training, support, and follow-up. Therefore, the present study aimed to determine the impact of successful breastfeeding training on the knowledge and planning of pregnant women regarding this behavior in 2018.Methods: This quasi-experimental study with a pre-/post-test design was carried out on 30 pregnant women with a gestational age of 32 weeks. At first, two comprehensive health centers were selected by cluster sampling. The dependent variable was successful breastfeeding, while the independent variables were awareness and planning for breastfeeding. The educational content was presented in three 45-minute sessions. Due to the lack of a standard questionnaire, a researcher-made questionnaire was prepared using the relevant references. After all, the data were entered into the SPSS 22 software and were analyzed using paired t-test and ANOVA.Results: The mean score of the mothers’ awareness of successful breastfeeding was increased from 49.97±3. 53 to 63.27±3.72 and that of their planning for successful breastfeeding was increased from 42.78±2.99 to 53.77±3.74; these differences were statistically significant (P<0.001). The results revealed no significant relationships between the mothers’ demographic characteristics and the questionnaire scores.Conclusion: Successful breastfeeding training can improve awareness and planning for breastfeeding, which can lead to the continuation and promotion of this behavior.